2007
DOI: 10.1038/sj.npp.1301471
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacological Profiles of Morphine and Oxycodone under a Neuropathic Pain-Like State in Mice: Evidence for Less Sensitivity to Morphine

Abstract: The present study was undertaken to investigate pharmacological actions induced by morphine and oxycodone under a neuropathic pain-like state. In the m-opioid receptor (MOR) binding study and G-protein activation, we confirmed that both morphine and oxycodone showed MOR agonistic activities. Mice with sciatic nerve ligation exhibited the marked neuropathic pain-like behavior. Under these conditions, antinociception induced by subcutaneously (s.c.) injected morphine was significantly decreased by sciatic nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 41 publications
7
60
0
Order By: Relevance
“…The antinociceptive effect of oxycodone on ambulatory and neuropathic pains was almost equal to that on ongoing pain, however, the antinociceptive effect of morphine on ambulatory and neuropathic pains, and that of fentanyl on ambulatory pain were different from those on ongoing pain. Oxycodone, as well as morphine and fentanyl, is a µ-opioid receptor agonist and the intrinsic activity of oxycodone to the µ-opioid receptor is weaker than that of morphine and fentanyl [3]. The different profile of each opioid on ongoing, ambulatory and neuropathic pains could not be explained by either the different binding property to the µ-opioid receptor or the different brain penetration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antinociceptive effect of oxycodone on ambulatory and neuropathic pains was almost equal to that on ongoing pain, however, the antinociceptive effect of morphine on ambulatory and neuropathic pains, and that of fentanyl on ambulatory pain were different from those on ongoing pain. Oxycodone, as well as morphine and fentanyl, is a µ-opioid receptor agonist and the intrinsic activity of oxycodone to the µ-opioid receptor is weaker than that of morphine and fentanyl [3]. The different profile of each opioid on ongoing, ambulatory and neuropathic pains could not be explained by either the different binding property to the µ-opioid receptor or the different brain penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Oxycodone has a high selectivity for the µ-opioid receptor with apparent agonistic activity, but the binding affinity of oxycodone to the µ-opioid receptor is weaker than that of other opioids. Specifically, the affinity of oxycodone to the µ-opioid receptor is 1/10 that of morphine [1,2,3]. Regardless of the relatively low receptor affinity, several reports have demonstrated that oxycodone induces obvious antinociception on thermal and mechanical stimuli in several animal models [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a mouse femur bone cancer (FBC) model, which showed similar pathological symptoms to human bone metastasis, morphine and fentanyl were reported to exhibit antinociceptive effects on several pain-related behaviors (19). Although those studies showed that these opioids were effective on several different types of pain, only a few studies have directly compared the pharmacological efficacy of the three opioids in animal pain models (17). For an appropriate opioid use, it is important to understand the pharmacological profile of each opioid in various types of pain.…”
Section: Introductionmentioning
confidence: 99%
“…These opioids exhibited the significant antinociceptive effects, as measured by the tail-flick test, on pain caused by thermal stimuli (17). In the mouse sciatic nerve ligation (SNL) model, oxycodone has been shown to reverse the nociceptive pain caused by mechanical stimuli (18).…”
Section: Introductionmentioning
confidence: 99%